Art Music by Caribbean Composers: Jamaica - Gangelhoff, Christine; LeGrand, Cathleen (International Journal of Bahamian Studies, 2011)
Jamaica is among the Caribbean islands that Columbus claimed for Spain. In response to its rich diversity of peoples: Europeans, Asians, Chinese, Indians and Africans, the motto of Jamaica is: Out of Many, One People."Jamaican music is as varied as the people who inhabit the island... [M]uch folk music retains features and functions of black African music, blended with elements of European (primarily British) music" (Lewin & Gordon, 2007-2011). Jamaican musical genres, such as ska, rocksteady, reggae, and dancehall, are popular and influential internationally.The classical music tradition in Jamaica dates back to the 18th century.